PSYCHO-SUFISTIC THERAPY OF UNDERGROUND SUFISM MOVEMENT:A HEALING METHOD AGAINST PUNK COMMUNITY IN JAKARTA - Muaz, Abdul; Ahmad, Adang Darmawan (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
This study imvestigates the psycho-Sufistic therapy applied by the "Tasawuf Underground" movement to the Punk community in Jakarta. The phenomenon of the Punk community in big cities is often neglected by Muslim preachers. The spiritual condition of the Punk community are hardly taken into an account nowadays. It is because of stereotypical and pejorative stigmas  that make them  far from religious values. Therefore, the Tasawuf  Underground movement attempts to approach and invite them to migrate spiritually (hijra) in gentle and interactive ways. This study aims to reveal the Sufistic approach model practiced by Tasawuf Underground in the process of migrating the punk community and homeless juvenile in the capital city of Jakarta to comprehend their religion and life. The research employs a qualitative description by conducting observation and interviews. As the data obtained,  they are  analyzed by using the perspective of Suluk method in Sufism  and the humanistic-physcology theory by Abraham Maslow. The result of study indicates that the Tasawuf Underground movement implements an excellent psycho-Sufistic method to be used as a role model to deal with punk communities and similar marginalization elsewhere.